Are data available for tracking progress on nutrition policies and programs in South Asia? - Jangid, Manita; Neupane, Sumanta; Murira, Zivai; Auer, S.R.; Scott, Samuel P.; Menon, Purnima (International Food Policy Research Institute, 2021)
The World Health Organization (WHO) and other global nutrition and health agencies recommend nutrition actions throughout the life-course to address malnutrition in all its forms. As global recommendations are updated based on available evidence, it is anticipated that governments and stakeholders will, in turn, build on these recommendations to update national policies and programs. Little is known in the South Asia region about coherence with globally recommended actions. Even less is known about the degree to which countries are able to track their progress on nutrition actions. To address the gap, this brief summarizes the and program gaps in addressing nutrition actions, along with data gaps in population-based surveys in all the countries in the South Asia region, including Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka.